THE SOCIOLOGY OF WEB 2.0 - بن عمار, سعيدة خيرة (International Journal of Social Sciences, 2015)
Web 2.0 starts from people to people, a user is the producer of digital content and he is the consumer of it interchangeably with other users and it is not necessarily for all users to be producers, some of them settle for only browsing the web, also the web create social relationship between users like online relationship or maintain other offline relationship, in this part we will introduce an initiation in the sociology of web2.0 or social web to identify what is social in social web? and how social web changes social relationship between individuals?. Social web is a platform that functions to connect people and facilitate communication, collaboration and participation for them within a relations network characterized through a set of communicative tools and applications called web2.0 applications represented in blogs, social networks sites, wikis, discussion forum, micro-blogging…etc… they call it social web because it connects people and help them to build communities and create or maintain offline/online relationship, where Christian Fuchs indicates that:”social networks platforms (we will detailed in another chapter) is the ideal example expressing what is termed web2.0, that it enable maintaining and building social relationship”. Adding:”web2.0 applications like social networking platforms keep individuals busy generating personal information that they display online in social networking profiles, blogs..Etc, most of these application are built in such way that each participant has his/her own space that he/she creates and maintains.
Keywords: web 2.0, social, networks, social capital